THE EFFECT OF ADDING GARLIC FLOUR (Allium Sativum) AND OREGANO LEAVES (Oreganum Vulare) ON THE HISTOPATHOLOGICAL QUALITY OF THE HEPAR OF BREAKER CHICKENS - Amini, Khairuni; Indrati, Rositawati; Sjofjan, Osfar (Penerbit Lafadz Jaya, 2023)
This study aims to determine the results of adding garlic flour (Allium sativum) and oregano leaves (Oreganum Vulare) to feed on the liver histopathology of broiler chickens. This research consisted of 2 stages, the research material for stage 1 was a descriptive analysis of the histopathological changes in the liver of embryonated chicken eggs (TAB). The research material for phase II was the 200 Day Old Chick (DOC) Ross strain, unsex. Average body weight 38.485 ± 0.90 g. The research method used laboratory experiments and field experiments using a completely randomized design (CRD) with 5 treatments and 5 replications. The treatments given were P0: Basal feed (control feed), P1: Basal feed plus 0.25% garlic flour, P2: Basal feed plus 0.5% garlic flour, P3: Basal feed plus 0.75% white onion flour, P4: Basal feed plus 1 % garlic flour. The variables measured in stage I were liver histopathological changes. The data obtained will be analyzed descriptively. The variables measured in stage II, namely the enzymes ALT, AST, and ALP, liver weight, and abdominal percentage obtained will be statistically analyzed using analysis of variance (ANOVA) from a Completely Randomized Design (RAL) and followed by an honest significant difference test ( BNJ) or Tukey's test. The results of the research were that giving garlic flour in feed influenced the parameters used. The use of garlic flour in feed had a very significant effect (P<0.01) on histopathological changes, changes in ALT, AST and ALP enzymes. The conclusion obtained in this research is that the addition of 1% garlic flour to broiler chicken feed provides the best productivity.